A case of familial phaechromocytoma- was it? - Zahari Sham, Siti Yazmin; Umar, Nor Aini; Mazlan, Khalidah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
With advancement in genetic studies, familial phaeochromocytoma (PCC) and paraganglioma (PGL) are increasingly being recognized. Characteristically, correlations exist between genotypes and clinical and biochemical phenotypes. We report a phaeochromocytoma in a young patient with intriguing family histories, raising the possibility of his being a familial case.